Giant Solitary Plasmacytoma of Skull: A Case Report - Islam, KM Tarikul; Jahan, Nowshin; Bhattachariya, Razib; Halder, Rathin; Md Hafiz, Ahsan; Alam, Shamsul; Haque, Moududujl; Hossain, ATM Mosharef (Bangladesh Journal of Neurosurgery, 2019)
Plasmacytoma is a tumor arising from plasma cell, which mainly grows within soft tissue or within axial skeleton, when it is present as a discreet solitary mass it is called as solitary plasmacytoma & it is rare, we report a 46 years male, presented to us with the complaints of painless swelling in the left front parietal region which is about 8.6x6.5cm in diameter, Magnetic resonance imaging revealed an extra axial mass in fronto parietal region with overlying bone destruction mimicking meningioma with bony erosion, we did frontoparietal craniectomy and complete resection of tumor with bone margin subsequent cranioplasty also done, histopathology of which revealed plasmacytoma,after that we did urinary bence jones protein which was negative Bang. J Neurosurgery 2019; 8(2): 115-118